Development Of Strategic Methods For Family Balanced Counseling (SKB KB) On The Selection Of Potential Acceptance Contraception Tools In Makassar - Sitti Mukarramah; Indriani; Zulaeha A. Amdadi (Publisher Cv. Inara, 2021)
Family planning is a strategy to reduce maternal mortality, especially mothers with 4T conditions. Counseling plays an important role in achieving quality family planning services. A balanced counseling strategy (SKB) began to be developed and adapted for use in 2016, to strengthen postpartum family planning counseling services (KBPP). The purpose of this study was to determine the effect of the Family Planning Balanced Counseling Strategy (SKB-KB) on the choice of contraceptives at Kassi-Kassi Community Health Center Makassar City. The type of research used is Quasi Experimental (quasi-experimental). This study conducted an intervention in both groups by assessing before and after treatment / counseling. One group intervened with the SKB-KB method, while the other group intervened with the ABPK method. Data were analyzed using the chi square test with a significance level of p <0.05. The results showed that the SKB-KB method had an influence on the choice of contraceptives between the intervention group and the control group (p: 0.0008; ? 0.05).